Adaptive Parotid Gland Hypertrophy Induced by Dietary Treatment of GSE in Rats. (August 2014) - Inoue, Kaoru; Morikawa, Tomomi; Matsuo, Saori; Tamura, Kei; Takahashi, Miwa; Yoshida, Midori
In a 13-week feeding toxicity study of grape skin extract (GSE) performed previously, 5.0% GSE showed diffuse hypertrophy and basophilia in rat parotid glands. To clarify whether the change in the parotid glands was an adverse effect of GSE, 6-week-old male F344 rats were fed a diet containing 5.0% GSE or were administered a dose corresponding to the dietary concentration via gavage for 4 weeks, and the treatment was stopped for 2 weeks. To ascertain the effect of astringency, other animals were fed a diet containing 5.0% tannic acid (TA) using the same protocol as the GSE feed group. Control groups were fed a basal diet or were administered sterilized distilled water by gavage. In the GSE and TA feed groups, diffuse severe hypertrophy and basophilia in the parotid glandular epithelial cells were observed. Macroscopic, microscopic, and ultrastructural characteristics consistent with cellular hypertrophy was less apparent after the recovery period in both feed groups. In contrast, no changes were observed in the parotid glands of the gavage GSE and control groups at week 4. Based on these findings of parotid hypertrophy without cytotoxicity, the data from this and previous studies suggest that hypertrophy of the parotid glands induced by feeding treatment with GSE is an adaptive non-adverse effect that is reversible upon removal of the sialotrophic agent.